2017
DOI: 10.1128/aem.03295-16
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Growth Modeling of Environmental and Clinical Legionella pneumophila Multilocus Variable-Number Tandem-Repeat Analysis (MLVA) Genotypes

Abstract: Legionella pneumophila causes waterborne infections resulting in severe pneumonia. High-resolution genotyping of L. pneumophila isolates can be achieved by multiple-locus variable-number tandem-repeat analysis (MLVA). Recently, we found that different MLVA genotypes of L. pneumophila dominated different sites in a small drinking-water network, with a genotype-related temperature and abundance regime. The present study focuses on understanding the temperature-depen dent growth kinetics of the genotypes that dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
6
35
0
Order By: Relevance
“…can also survive at temperatures below 20°C and even below freezing (Borella, Guerrieri, Marchesi, Bondi, & Messi, ). Sharaby et al () reported that environmental strains of L. pneumophila exhibited a superior capability for growth at lower temperatures (25 and 30°C) than did clinical strains. Moreover, as the virulence of L. pneumophila is temperature dependent, with maximum virulence between 37 and 42°C (Edelstein, Beer, & DeBoynton, ; Mauchline, James, Fitzgeorge, Dennis, & Keevil, ), the virulence of strains growing in drinking water systems needs to be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…can also survive at temperatures below 20°C and even below freezing (Borella, Guerrieri, Marchesi, Bondi, & Messi, ). Sharaby et al () reported that environmental strains of L. pneumophila exhibited a superior capability for growth at lower temperatures (25 and 30°C) than did clinical strains. Moreover, as the virulence of L. pneumophila is temperature dependent, with maximum virulence between 37 and 42°C (Edelstein, Beer, & DeBoynton, ; Mauchline, James, Fitzgeorge, Dennis, & Keevil, ), the virulence of strains growing in drinking water systems needs to be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, at lower temperatures (25°C) the opposite was observed (Sharaby et al, 2017). The identified emergence of new disease-associate clones of L. pneumophila may, in part, be accelerated by selective pressures exerted by heat treatments for disinfection.…”
Section: Pasteurization Selects For Thermal Tolerant Legionella Pneummentioning
confidence: 85%
“…7 in reference 43). Recently, Sharaby et al (37) demonstrated that the distribution and temperature preferences of these environmental genotypes were consistent with their temperature-dependent growth traits. For clinical isolates, it was shown that they had significantly higher growth rates and reached higher maximal cell densities at 37°C and 42°C than the environmental strains (37).…”
mentioning
confidence: 93%
“…Recently, Sharaby et al (37) demonstrated that the distribution and temperature preferences of these environmental genotypes were consistent with their temperature-dependent growth traits. For clinical isolates, it was shown that they had significantly higher growth rates and reached higher maximal cell densities at 37°C and 42°C than the environmental strains (37). These findings highlight the importance of studying and characterizing the physiological and virulence traits of different L. pneumophila genotypes in order to promote our understanding of the hazardous potential of pathogenic strains.…”
mentioning
confidence: 93%
See 1 more Smart Citation